2016
DOI: 10.3892/mmr.2016.5941
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the growth of human melanoma cells by methionine enkephalin

Abstract: Melanoma is an aggressive cancer, the incidence of which is increasing worldwide. Limited therapies are currently available, particularly following metastasis. The aim of the present study was to investigate the inhibiting effect of methionine enkephalin (MENK) on human melanoma via opioid receptors. The results of the present study revealed that MENK markedly regulates the proliferation of A375 cells, causing cell cycle arrest in G0/G1 phase and a decrease in the percentage of cells in S and G2/M phases. Reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Published data suggest that MENK also has an antiviral role during influenza 36 and HIV infections. 37 Moreover, MENK has significant immunotherapeutic activity against tumors in vivo, including ovarian, 21 pancreatic, 38 and head–neck cancers, 39 and can inhibit or delay tumor cell proliferation directly in vitro through cell apoptosis and/or cell cycle arrest, as reported in studies examining human melanoma, 10 triple-negative breast cancer, 24 and hepatoblastoma cancer cells. 40 The results from all these studies support these bioactivities mediated by OGFr ligation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Published data suggest that MENK also has an antiviral role during influenza 36 and HIV infections. 37 Moreover, MENK has significant immunotherapeutic activity against tumors in vivo, including ovarian, 21 pancreatic, 38 and head–neck cancers, 39 and can inhibit or delay tumor cell proliferation directly in vitro through cell apoptosis and/or cell cycle arrest, as reported in studies examining human melanoma, 10 triple-negative breast cancer, 24 and hepatoblastoma cancer cells. 40 The results from all these studies support these bioactivities mediated by OGFr ligation.…”
Section: Discussionmentioning
confidence: 97%
“… 5 The OGF not only has neuroendocrine 9 and immune regulation activity, but also has direct antitumor activity following binding to opioid receptors. 2 , 6 , 10 18 Naltrexone (NTX), an opioid receptor antagonist, can inhibit the effects of MENK during co-incubation, supporting its role in the bioactivity of MENK. 2 Data from previously published results from our laboratory indicated that MENK, in a dose-dependent manner, can inhibit tumor growth in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we demonstrated that MENK alone or in combination with IL-2 or IFN-γ, respectively strengthened the pathway between dendritic cells (DCs) and CD4 + T cells, and induced maturation of DCs with higher production of IL-12 ( 26 ). MENK was found to inhibit the growth and induce apoptosis of A375 cells ( 27 ). In the present study, we made the unique discovery that MENK not only can inhibit the proliferation and metastasis of B16 cells directly, but also can indirectly kill B16 cells by stimulating lymphocyte subsets and cytokine secretion to achieve the therapeutic goal.…”
Section: Discussionmentioning
confidence: 99%